Salinity Tolerance in Freshwater Drum (Aplodinotus grunniens): Investigating Biochemical, Antioxidant, Digestive Enzyme, and Gene Expression Responses to Acute Salinity Stress - Justice Frimpong Amankwah; Wu Jin; Xueyan Ma; Pao Xu; Haibo Wen; Kennedy Emeka Amuneke; Brian Pelekelo Munganga; Kang Li; Jingwei Liu; Hongxia Li (Animals)
Variations in salinity levels in aquaculture significantly influence fish physiology, impacting population dynamics and industry viability. This study aimed to examine the physiological response of the freshwater drum (Aplodinotus grunniens) to differing salinity conditions, assessing its potential for cultivation in brackish water environments. Fish averaging 45 ± 0.1 g were subjected to acute salinity tests across three groups: a control group at 0‰ and experimental groups at 7.5‰ and 15‰ over four days. The initial findings indicated that A. grunniens could tolerate salinity levels up to 15‰ without adverse effects. Key biochemical markers, such as aspartate aminotransferase and alanine aminotransferase, exhibited significant fluctuations but decreased over time. Antioxidant enzyme activity increased relative to the control, while malondialdehyde levels declined, indicating effective oxidative stress management. Additionally, digestive enzymes like amylase and lipase demonstrated adaptability to changing salinity. The expression of heat shock proteins 70 and 90 in the gills and livers varied initially but showed no sustained changes. Overall, the results suggest that A. grunniens possesses notable resilience to salinity variations, indicating its suitability for brackish water aquaculture and highlighting the optimal salinity ranges for promoting growth.